Regional digitalization and industry factors of labor productivity growth - Milekhina Olga; Adova Irina (π-Economy)
The article is devoted to the study of the results of regional digitalization and their impact on labor productivity. The main objective of the work is to assess the actual impact of investments in digitalization of industries on labor productivity growth in the regions of the Russian Federation. Achieving the goal of the study required solving the following problems: 1) selection and study of relevant publications and researchers' forecasts regarding the impact of digitalization on increasing labor productivity of the constituent entities of the Russian Federation; 2) designing a factual data field and collecting information on the impact of digitalization processes on labor productivity growth in Russian regions; 3) collection and analysis of data on the dynamics of labor productivity growth, indicators of the gross regional product of the constituent entities of the Russian Federation and industry returns on investments in digitalization; 4) drawing conclusions about the contribution of regional digitalization to increasing labor productivity. The design of the study is based on the consistent implementation of these tasks. In the course of the study, methods and approaches of statistical analysis, sequential decomposition, analysis and synthesis of complex systems were used. The work collects public data on forecasts on the impact of digitalization on increasing labor productivity in the regions of the Russian Federation. The created factual data field on the effectiveness of digitalization processes in the economies of the constituent entities of the Russian Federation made it possible to identify fourteen leading regions. The maximum values of the labor productivity index for 2020–2022 were demonstrated by three regions, the analysis of whose performance results formed the basis for the conclusions of this study. It is shown that the introduction of information and communication technologies in the short term did not have a significant impact on increasing labor productivity and a more in-depth analysis of managing people is needed to increase their productivity. It is concluded that the dynamics of the rate of productivity of economic activity is influenced by many endogenous and exogenous factors, and digitalization is only one of them. A selective analysis of the sectoral structure of the economy of the regions leading in digitalization showed an ambiguous contribution of high-tech industries to the creation of gross added value.